MOTIVASI DEFINISI INVERS MOORE PENROSE PADA RING DENGAN ELEMEN SATUAN YANG DILENGKAPI INVOLUSI - SRRM, Titi Udjiani (MATEMATIKA, 2016)
Development on the research of the  inverse  matrix until the Moore Penrose inverse matrix motivate researchers to conduct the research on the Moore Penrose inverse and the inverse of element in the ring with a unit element. The  used method  is  expanding the definition of   inverse in matrix to the ring with a unit element. Also  generalizing the  transpose  operation of matrix to  be a function of involution on the ring.